Creating a Responsible Renewable Energy Investment Model for the MENA Region’s Low-Carbon Transition - AlSiyabi , Maryam; Hassan , Hasmaizan; Khudari , Mohammed (Journal of Ecohumanism, 2024)
Addressing climate change presents specific challenges for the countries of the Middle East and North Africa (MENA), particularly concerning oil production and water scarcity, but it also offers opportunities for new paths toward sustainability. The transition to low-carbon energy raises significant concerns for oil and gas producers in the MENA region, especially regarding their dependence on hydrocarbon revenues. Without proper adjustments, this transition could worsen macroeconomic imbalances and potentially threaten existing social contracts. Policymakers are working to promote various renewable energy sources and implementation strategies to mitigate the adverse effects of climate change. As a result, the development of an index capable of accurately measuring and benchmarking a country’s overall sustainability and economic performance becomes essential. This index should provide a comprehensive assessment of both the current and future state of renewable energy. Additionally, it must highlight key environmental, social, governance (ESG), and economic factors within the renewable energy sector. This proposal aims to establish a composite index, referred to as the Renewable Energy Responsible Investment Index (RERII), covering 19 countries and utilizing 22 distinct metrics. The RERII trend is calculated from 2010 to 2019. The proposed index can serve as a screening tool, decision-making aid, benchmarking instrument, and guide for sustainable development.